Player versus Player: A systematic review of cyberbullying in multiplayer online games - Hu Yunhao; Evelyn Sophie; Clancy Elizabeth M.; Klettke Bianca (Computers in Human Behavior Reports)
Introduction: This systematic review evaluates the prevalence, characteristics, and predictors of cyberbullying behaviour in multiplayer online games. Methods: Following the PRISMA framework, seven databases were searched from inception until August 24th, 2024. Peer-reviewed journal articles and grey literature addressing cyberbullying within multiplayer online gaming environments were included, without constraints on study design or publication date. The quality of individual studies was assessed using the Joanna Briggs Institute Critical Appraisal tool. A total of 64 studies were included for analysis. Results: Findings revealed notable methodological variance, including a wide array of measurements and definitions of cyberbullying. Prevalence rates indicated that men are more likely to be both perpetrators and victims. Key themes such as anonymity, bidirectionality, competitiveness, and normalization emerged as potential predictors of cyberbullying in gaming. Common coping strategies included ignoring/blocking the perpetrator, and gender concealment for women. Organizational response to cyberbullying was mostly deemed to be insufficient by gamers. There was a paucity of studies examining the association between violent content exposure and cyberbullying in gaming. Discussion: While findings do not provide conclusive evidence on the main factors driving cyberbullying in online gaming, they underscore avenues for further research and intervention. Standardising definitions and methodologies can improve our understanding of cyberbullying behaviour. Implementing measures such as community-building features, delayed match statistics, and temporary communication freezes after character deaths may help curb impulsive cyberbullying.